Analisa Kekuatan Tekan, Daya Serap Air Dan Densitas Pada Material Komposit Berbahan Dasar Fly Ash Batu Bara, Arang Sekam Padi Dan Plastik HDPE - Irwan, Irwan; Mangalla, Lukas Kano; Kadir, Abd. (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
Utilization of waste or garbage in Indonesia continues to be carried out in line with the increasing number of which is used as a filler material in making composites. This study aims to determine the effect of composite material composition made from fly ash coal, rice husk charcoal and HDPE plastic on compressive strength, water absorption and density of the material. This research was conducted as an experimental study that had been carried out by means of laboratory tests. The composition used was 30%: 5%: 65%, 25%: 10%: 65%, 20%: 15%: 65%. Specimens were made to ASTM D695 standards for press testing. The results of this study indicate that the value of the compressive strength obtained at the composition of 30%: 5%: 65% is equal to 1.96 N / mm2, the value of water absorption in the largest composite material is at the composition of 20%: 15%: 65%, which is equal to 2,0283%, as well as for the density value of the largest composite material at the composition of 30%: 5%: 65% which is equal to 1.4692 g / cm3.Keywords: Fly ash coal, rice husk charcoal, HDPE Plastic, press, water absorption, density